2014
DOI: 10.3389/fimmu.2014.00264
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Gene Repertoire Diversification and Selection in the Stomach – From Gastritis to Gastric Lymphomas

Abstract: Chronic gastritis is characterized by gastric mucosal inflammation due to autoimmune responses or infection, frequently with Helicobacter pylori. Gastritis with H. pylori background can cause gastric mucosa-associated lymphoid tissue lymphoma (MALT-L), which sometimes further transforms into diffuse large B-cell lymphoma (DLBCL). However, gastric DLBCL can also be initiated de novo. The mechanisms underlying transformation into DLBCL are not completely understood. We analyzed immunoglobulin repertoires and clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 88 publications
4
30
0
Order By: Relevance
“…Clonally related sequences (based on VDJ segment identity and CDR3 similarity) were aligned using the well-known sequence alignment tool ClustalW2 [38], in order to confirm that the CDR3 in the clonally related sequences were highly homologous. Further analyses were done using our automated pipeline for analyzing Ig gene sequences [39].Estimates of the full repertoire from which each sample were taken, diversity measures and similarity indices of the estimated repertoires were calculated using SPADE C [40], as described in detail in [41]. Briefly, alpha measured the diversity of an individual sample, gamma diversity represents the "global" repertoire diversity across all samples studied in each group of samples, and beta represents the diversity component resulting from the variability between individual repertoires or samples (beta = gamma/alpha).…”
mentioning
confidence: 99%
“…Clonally related sequences (based on VDJ segment identity and CDR3 similarity) were aligned using the well-known sequence alignment tool ClustalW2 [38], in order to confirm that the CDR3 in the clonally related sequences were highly homologous. Further analyses were done using our automated pipeline for analyzing Ig gene sequences [39].Estimates of the full repertoire from which each sample were taken, diversity measures and similarity indices of the estimated repertoires were calculated using SPADE C [40], as described in detail in [41]. Briefly, alpha measured the diversity of an individual sample, gamma diversity represents the "global" repertoire diversity across all samples studied in each group of samples, and beta represents the diversity component resulting from the variability between individual repertoires or samples (beta = gamma/alpha).…”
mentioning
confidence: 99%
“…Thus, to evaluate over-or underrepresentation of clonotypes, the frequency of certain segment combinations should be compared with the expected frequency if all gene segments were expressed independently. 47 Under the latter assumption, the expected probability of observing a given combination V x J y , P(V x J y ), is the product of the probabilities of observing each of these segments, i.e., P(V x )*P(J y ); the latter probabilities are the observed frequencies of each segment in the database (see appendix in ref. 48).…”
Section: Analysing B-cell Repertoires: Gene Segment Usage and Identifmentioning
confidence: 99%
“…Sequence data were processed as described [41] [44]. Briefly, an in-house program deletes duplicate sequences (which might be a product of PCR amplification), and leaves only the unique sequences for the analysis.…”
Section: B Data Processingmentioning
confidence: 99%
“…Previous studies demonstrated the usefulness of this method and resulted in new insights regarding differences in GC dynamics in aging or between different tissues [35]- [37],in autoimmune diseases [38], chronic inflammation [39], lymphomas [40], and chronic gastritis and gastric lymphomas [41]. This method was also used to determine clonal relationships of Ig genes from different tissues [39] [42].…”
Section: Introductionmentioning
confidence: 99%